CD24 Ala57Val polymorphism is associated with spontaneous viral clearance in the HCV‐infected Chinese population. (19th March 2014) - Sun, Haibo; Pan, Yu; Wu, Ruihong; Lv, Juan; Chi, Xiumei; Wang, Xiaomei; Tu, ZhengKun; Zhong, Jin; Sun, Bing; Liu, Yang; Jiang, Jing; Niu, Junqi
Abstract Background & Aims Host immune response to hepatitis C virus (HCV) is a vital factor involved in both viral clearance and liver disease pathogenesis. CD24 plays an important role in inflammation and immune response and CD24 polymorphisms are associated with risk and progression of chronic hepatitis B virus infection. Our study evaluated whether CD24 polymorphisms affect HCV clearance. Methods We genotyped 544 chronic hepatitis C (CHC) patients, 78 spontaneous hepatitis C clearance (SHC) patients and 215 healthy controls for CD24 gene variants at positions −P534, P170, P1527 and IFNL3 rs12979860 by pyrosequencing. In CHC patients, 362 individuals were treated with a recombinant IFN‐α2b/ribavirin combination for 48 weeks and were followed up for an additional 24 weeks. Lymphocyte CD24 expression was analysed by flow cytometry. Results We show that P170 CT and CT/TT genotypes were over‐represented in the SHC group compared to CHC patients (62.8% vs. 47.2% and 75.6% vs. 60.3%, for respective polymorphisms). In multivariate logistic analysis, P170 (CD24 Ala57Val) polymorphism was an independent predictor of SHC (adjusted OR = 2.11, 95%CI = 1.19–3.73, P = 0.010 for CT genotype; OR = 2.01, 95%CI = 1.15–3.49, P = 0.014 for CT/TT genotype). No significant associations were found between the CD24 polymorphisms and treatment‐induced viral clearance in log‐rank analysis and Cox regression analysis. Patients with the CT/TT genotype had greater T‐cell CD24 expression than patients with the CC genotype. Conclusions Our findings suggest that CD24 Ala57Val polymorphism and associated variations in CD24 expression may be an important predictor for SHC, but have no effect on antiviral drug treatment response in Chinese CHC patients.